A New Bus Assignment Algorithm for a Shared Bus Switch Fabric. Issue 4 (2000) - Torres, D.; Gonzalez, J.; Guzman, M.
Abstract : An architecture for a Cell Switch Fabric (CSF) with a new bus assignment strategy is presented. The proposed architecture has a modular structure with a chip partitioning oriented to avoid the system from falling down totally, thus achieving expandability and increasing reusability. A discussion about different algorithms for the bus assignment is given. The shared bus is assigned in a cyclic and rotative way, switching microcells instead of cells. The CSF is built in four PCBs where every one has a capacity for four ports at 164.323 Mbps, the external port rate is 155.52 Mbps. A microcontroller realizes some tests and communicates with a PC, which runs a test, verification and CSF configuration program. Some parameters about the CSF behavior are measured too. Each Port was implemented on a CPLD FLEX10K100 and the Switch Control Block on a circuit MAX7128, both from Altera Company.